Harmonizing unemployment and sickness insurance: Why (not)? - Laura Larsson (Institute for Labour Market Policy Evaluation (IFAU), 2004)
The paper discusses harmonization of unemployment insurance (UI) and sickness insurance (SI). The focus is on the difference between the benefit ceilings in the two insurance systems that has been shown to affect the behavior among unemployed SI recipients. The four conclusions are: (i) It is difficult to argue that the design with different benefit ceilings of UI and SI would be optimal. (ii) During the study period 19982001, unemployed were overrepresented among SI recipients. (iii) Some of the overrepresentation is due to the different benefit ceilings. Thus, harmonization of the systems is motivated; (iv) In a complex system as the Swedish social insurance system, reducing moral hazard in one group probably also implies various indirect effects. When designing a reform, all insurances should be considered simultaneously.
Keywords: H51; H55; I18; J65; 330; Government policies; moral hazard; sickness insurance; unemployment insurance